Implementing TPACK in Social Science Subjects for Learning Recovery Post-Pademic - Rahma, Laula Ika Setya; Zakso, Amrazi; Rustiyarso, Rustiyarso (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study delves into the "Implementation of Technological Pedagogical and Content Knowledge (TPACK) in Social Science Subjects as an Effort to Recover Learning Post-COVID-19 Pandemic at SMA Negeri 4 Pontianak." It involves in-depth interviews to explore the application of TPACK, its effectiveness, and the challenges teachers encounter in its implementation. The findings indicate that the adoption of TPACK has had a positive impact on the quality of post-pandemic learning. Teachers effectively utilized technology to enhance engagement, relevance, and interactivity of learning, as well as to simplify the explanation of case studies. However, some TPACK indicators were not fully implemented, highlighting the need for further training. The study also uncovered challenges such as limited technology infrastructure, technical difficulties, access issues, and time constraints, which impede the creation of an optimal learning experience at SMA Negeri 4 Pontianak.